PHENOMENON OF POSITIVE LIABILITY: CRITICAL ANALYSIS - Duyunov, Vladimir; Zakomoldin, Ruslan (Revista Inclusiones, 2020)
The article criticizes the existing scientific views on the concept of positive legal responsibility. Their followers believe that liability is a type of social responsibility and can be not only retrospective but also positive. In this regard, there are sufficient grounds for emphasizing and consolidating the concept of "positive legal responsibility" in science and law. The authors of the article substantiate the opposite view that the introduction of the concept of "positive legal responsibility" into scientific use, legislation and law enforcement can confuse and create difficulties in both legal understanding and law enforcement. The article analyzes cons, weak spots and contra-dictions of the abovementioned approach. The authors argue that the positive aspect of social responsibility is its scientific abstraction from morality, psychology, pedagogy, sociology and philosophy that has roughly the same meaning in all spheres of social life and there is no reason or ground to materialize it and divide into types, including in the field of law. While considering the debatable issue of "positively responsible" behavior and its boundaries, the authors have concluded that this concept does not include the subject's behavior that complies with legal requirements but violates other social norms.